O FEMINISMO NO BRASIL ATUAL E AS REDES SOCIAIS DIGITAIS - Pinheiro, Naira Leticia Giongo Mendes; Schwengber, Maria Simone Vione; Conceição, Cauana Peyrot; Brachtvogel, Caterine De Moura (Salão do Conhecimento, 2019)
Pesquisa em andamento no curso de Doutorado em Educação nas Ciências